ANALISIS PEMANFAATAN BINA KELUARGA LANSIA (BKL) OLEH KELUARGA YANG MEMPUNYAI LANSIA GUNA MENCIPTAKAN LANSIA TANGGUH - Eva Mayasari; Riska Epina Hayu; Sumandar Sumandar (Al Tamimi Kesmas: Jurnal Ilmu Kesehatan Masyarakat (Journal of Public Health Sciences), 2022)
The increasing life expectancy and decreasing death rates have resulted in an increase in the number of elderly people. In Indonesia, the percentage of elderly people has increased, in 2019 it doubled to 9.6 percent where the number of elderly women was one percent more than the number of elderly men (10.10 percent compared to 9.10 percent). Young elderly (60-69 years) reached 63.82 percent, middle elderly (70-79 years) reached 27.68 percent and old elderly (80 years and over) reached 8.50 percent. The purpose of this study was to determine the use of Elderly Family Development (BKL) by families who have elderly. This research is a quantitative research by distributing questionnaires to 310 respondents in the KB Berkah Bersama Village, Bukit Raya District, Pekanbaru City. The results of the evaluation revealed that there was no relationship between the variables of knowledge, attitude, distance and family support on the use of Elderly Family Development (BKL) by families who have elderly